Who Turns the Green Gear? Stakeholder and TPB, Environmental Uncertainty, and the Finance Innovation Performance Chain in Chinese SME - Yuran, Gao; Anwar, Ahsan (International Journal of Energy Economics and Policy, 2025)
Chinese small and medium-sized enterprises experience pressure to be “green” in pursuit of green finance, as the Chinese government has established dual-carbon goals in addition to the Sustainable Development Goals (SDG). This paper applies the Theory of Planned Behaviour, Stakeholder Theory, and the concept of environmental uncertainty to explain the process by which green finance intentions lead to green innovation and to further understand the sustainability implications in terms of their impact on triple-bottom-line performance. Drawing on a SmartPLS analysis of 526 SMEs across nine Chinese cities, we find that managers’ green attitudes and peer-driven norms are the primary drivers of financing intent; self-efficacy and supportive conditions indirectly boost intent via perceived control. Green leadership and environmental literacy forge positive attitudes, while regulatory and competitive signals reinforce norms. Once intention crystallizes into funding, SMEs unlock green innovations that yield clear economic, social, and environmental returns. Even amid turbulence, regulatory mandates and managerial confidence remain reliable anchors. These findings provide a roadmap for policymakers to issue stable and transparent green finance mandates. Financial institutions can tailor their credit based on behavioral cues, and SMEs should invest in leadership and capacity building.